The THE ROLE OF SELF CONTROL TO MEDIATE THE INFLUENCE OF ACHIEVEMENT MOTIVATION TOWARDS ACADEMIC PROCRASTINATION - Marliyah, L; Novera, D A (Unnes Science Education Journal, 2019)
This bottleneck phenomenon also occurs at the Faculty of Economics of UNNES where based on these data shows that, on average, graduates of the Faculty of Economics do postponement of thesis work with a study period more than 4 years. Academic procrastination disposed delay to finishing the final project and did other’s activity, and thus makes obstruction and the final project can’t be accomplished on time. It causes the decrease of productivity and individual work ethic and to creates low human quality. This study aimes to analyze the theoretical influence and case study related achievement motivation toward academic procrastination and self control as intervening variable. Data is collected using questionnaires. Sample is obtained by employing convenience sampling technique. In addition, the data is analyzed using descriptive analysis and regression analysis. The result of the study showed that achievement motivation had not effect significanly on academic procrastination and this study finds that the role of self control to mediated the influence of achievement motivation toward academic procrastination. It is suggested that there should be a good employment creation which can lower the level of academic procrastination and propel the acceleration of country’s economy to decrease educated unemployed that may increase poverty.